Morphomolecular analysis of the immune tumor microenvironment in human head and neck cancer - Badr, Mohamed; Jöhrens, Korinna; Allgäuer, Michael; Boxberg, Melanie; Weichert, Wilko; Tinhofer, Ingeborg; Denkert, Carsten; Schirmacher, Peter; Stenzinger, Albrecht; Budczies, Jan (Cancer immunology immunotherapy, 2019)
Immunotherapy is effective in head and neck squamous cell carcinoma (HNSCC), but only a minority of patients responds to immune checkpoint blockade (ICB). To contribute to a better understanding of the underlying immune biology, we combined histomorphological evaluation and molecular analysis of the HNSCC immune microenvironment in the TCGA cohort. Analyzing digital HE-stained slides, a method for classification of tumor infiltrating lymphocytes (TILs) in the intra-epithelial compartment (ieTILs, present vs. absent) and the stromal compartment (strTILs, high vs. low) was established. We also analyzed the abundance of eight immune cell populations (estimated from RNAseq data) and PD-L1 mRNA expression. Status of ieTILs and status of strTILs were concordant for 61%, but discordant for 39% of tumors. In univariate survival analysis, ieTILs were a positive prognostic marker for DFS in the study cohort (HR = 0.66, p = 0.015) and in the HPV− subcohort (HR = 0.68, p = 0.04), but not in the HPV + subcohort. T cells were a positive prognostic marker for DFS in the study cohort (HR = 0.80, p = 0.03) and in the HPV + subcohort (HR = 0.20, p = 0.001), but not in the HPV− subcohort. In univariate survival analysis, PD-L1 mRNA expression was neither associated with DFS nor with OS. However, in bivariate and multivariate analyses including both PD-L1 mRNA levels and T cells, PD-L1 was a negative prognostic marker of DFS and OS, while T cells remained a positive prognostic marker. In conclusion, ieTILs and strTILs were non-redundant biomarkers in HNSCC and should be evaluated separately. The identified prognostic markers should be evaluated for predictivity in ICB-treated patients.